Epigenetic silencing of miR-708 enhances NF-κB signaling in chronic lymphocytic leukemia - Bär, Constance; Oakes, Christopher C.; Ruppert, Amy S.; Claus, Rainer; Kim‐Wanner, Soo-Zin; Mertens, Daniel; Zenz, Thorsten; Stilgenbauer, Stephan; Byrd, John C.; Plass, Christoph (International journal of cancer, 2015)
MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression and their deregulation is involved in tumor development. Epigenetic gene silencing in cancer by DNA methylation contributes to the silencing of tumor-suppressor genes, including miRNAs. We have recently shown that the promoter of miR-708 is aberrantly methylated in chronic lymphocytic leukemia (CLL). To characterize the molecular signaling networks that are influenced by miR-708, we performed a luciferase-based screen evaluating the effects of ectopic miR-708 expression on leukemia-relevant signaling pathways. We found that miR-708 strongly repressed NF-κB signaling, a pathway known to be deregulated in CLL. Among the predicted miR-708 targets was IKKβ (inhibitor of kappa light polypeptide gene enhancer in B cells, kinase-β/IKBKB), a key kinase facilitating NF-κB signaling. We validated the interaction of miR-708 with the 3′-untranslated region of IKKβ and found that miR-708 overexpression represses endogenous IKKβ. Phosphorylation of the IKKβ target IκBα and expression of known NF-κB target genes were impaired by miR-708. Furthermore, we identified an enhancer region downstream of the miR-708 promoter that displays a distinct DNA methylation status in CLL. High enhancer methylation is significantly correlated with lower miR-708 expression and is predominantly found in patients with poor prognosis and shorter time to treatment. These results demonstrate that miR-708 regulates the NF-κB pathway by targeting IKKβ, and that methylation of a key enhancer region contributes to its suppression in CLL.